Oceanographic Data of the 48th Japanese Antarctic Research Expedition from December 2006 to March 2007 - スズキ, エイイチ; スギモト, アヤ; SUZUKl, Eiichi; SUGIMOTO, Aya (National Institute of Polar Research, 2010)
P(論文) departmental bulletin paper